Administration of broccoli extract (Brassica oleracea var. italica) inhibited the increase of malondialdehyde level and the decrease of aortic endothelial cells in male wistar rats (Rattus norvegicus) exposed by cigarette smoke - Hayatul Firi; I Gusti Made Aman; Gde Ngurah Indraguna Pinatih (Fakultas Kedokteran Universitas Udayana, 2019)
Introduction: In the environment, there are many free radicals for the body, one of them is cigarette smoke which can cause oxidative stress conditions and result in damage to body cells. The broccolis extract containing flavonoids, glucosinolates, vitamins C, E and beta-carotene which have a high antioxidant protective effect. Methods: An experimental post-test only control study was conducted using 36 males Wistar rats, aged 10-12 weeks, and 200-300 gr weight which were divided in 2 groups (control and treatment group). The broccoli extract (120 mg/ 200 grBB) was given to treatment group one hour before exposure to cigarette smoke. After 28 days of the treatment, the rats were taken for examination of MDA levels and underwent a surgery for aortic tissue for endothelial histopathology examination. Results: The Finding indicated that the data were in normal distribution through data analysis of the Shapiro Wilk test. Lavene’s test showed that both the data distribution and variety of both groups was homogenous (p>0.05). Through independent t-test, there were significant differences between the two groups on the value of MDA and aortic endothelium number (p <0.05) as the result of the comparison result of both groups. Conclusion: The administration of broccoli extract (Brassica oleracea var.italica) inhibits the increased levels of blood malondialdehyde and a decreased of aortic endothelial cells in Wistar male rats exposed to cigarette smoke.